Human Resource Management at Dompet Dhuafa Institution in Indonesia - Johari Johari (International Forum of Researchers and Lecturers, 2023)
Recognizing zakat holds value in both the horizontal dimension, connecting Allah with humans, and the vertical dimension, connecting humans with one another, aligns with the principles that giving zakat, infaq, and sadaqah are integral to the obligations of the Muslim community. Efficient management of these allocated funds requires competent human resources to ensure that the financing reaches its rightful beneficiaries. This study investigates the phenomenon of human resources within zakat institutions based on the tasks and responsibilities carried out, which are notably complex. It underscores the influential role of human resources in the performance of zakat institutions. Human resources play a crucial role as professional assets for zakat administrators, adhering to specific standards. This writing aims to comprehend the strategic role of human resource management in zakat fund administration through a review of literature, legal regulations, and empirical evidence